Resposta comportamental de Diaphorina citri Kuwayama (Hemiptera: Psyliidae) a compostos voláteis de plantas não-hospedeiras - Monteiro, Neville Vieira (2023)
Citrus farming is an important activity for Brazilian agribusiness. However, the occurrence of insect pests and diseases causes losses to citrus orchards. Among the insect pests in citriculture, the psyllid Diaphorina citri Kuwayama (Hemiptera: Psyliidae) stands out as a vector of Candidatus Liberibacter spp., bacteria associated with HLB disease. As an alternative for controlling the psyllid, studying the influence of volatile organic compounds (VOCs) from non-host plants on the behavior of this pest can help reduce the incidence of HLB in citriculture. Thus, the objective of this study was to evaluate the behavioral response of D. citri to volatiles from non-host plants, such as acerola, cashew, guava and mango, as well as to identify the chemical compounds present in the volatile constitution of these plants. A four-arm olfactometer was used to determine the behavioral responses of D. citri females to volatiles. Three olfactometer arms containing non-host plants were compared with a control arm (air). Four series of trials were conducted: (1) cashew versus air, (2) mango versus air, (3) acerola versus air, and (4) guava versus air. An adult female of virgin D. citri up to 5 days old, without food for 24 hours, was placed through a small hole in the central area of the olfactometer. The insect was exposed to volatiles for 10 minutes, recording the residence time and the number of entries of D. citri in the arms of the olfactometer. The extraction of plant volatiles was performed by headspace solid phase microextraction (HS-SPME) and identified by gas chromatography coupled to a mass spectrometer (GC-MS). D. citri residence time data in the olfactometer arms were submitted to paired testes (P < 0.05). Data referring to the number of D. citri entries in the olfactometer arms were compared using the χ² test (α = 0.05). Significant differences were observed in the residence time for the treatments acerola versus air and cashew versus air, in wich D. citri spent more time in the control arm. The number of female entries of D. citri in the olfactometer arms with acerola, cashew and guava seedlings was significantly lower in relation to the control arm. For the mango versus air treatment, there was no significant difference. The analysis of volatiles from non-host plants revealed a predominance of terpenoid compounds. Thus, it is possible to infer that the volatile compounds present in acerola, cashew and guava are potentially repellent of D. citri.